Impression management by information technology professionals when reporting flow at work: A study at the individual and team levels of occupational culture - Jr. de Moura; Carlo G. Porto-Bellini; Eusebio Scornavacca (Administrative Sciences, 2025)
Information technology (IT) professionals have been depicted as good examples of in-flow individuals and teams. Accordingly, their workplace is acknowledged as ludic and relaxed, while also immersive and productive. The present study discusses evidence of actions effected by IT professionals to institutionalize and reinforce this mostly positive image when they report perceptions about themselves, their cohorts, and their routines at work. The study involves the processing of two datasets of responses given by IT professionals to questionnaires on the state of flow at work concurrently with other phenomena of positive psychology at both the individual and team levels. The datasets included contrasting (positive and negative) attitudinal measures that enabled a statistical discussion on whether IT professionals overestimate the positive aspects of their profession. This study concludes that cognitive dissonance and practices of impression management are likely involved in how IT professionals address flow-related questions to reinforce a positive image at work. Recommendations for scholars and industry researchers involve better questionnaire-crafting techniques to minimize measurement and inference biases, as well as contrasting self-reports with actual behaviors to build stronger indicators of the work climate, the routines, and the mood of IT personnel.
Keywords: 350; information technology culture; impression management; cognitive dissonance; flow; answering bias; psychometric research